Hadith #4370 - Sahih al-Bukhari - Ikrama عكرمة (Sahih al-Bukhari)
Ibn `Abbas said ( regarding the verse), “And when the relatives and the orphans and the poor are present at the time of division, “this verse and its order is valid and not abrogated.”
Grade: Sahih

Hadith #5669 - Sahih al-Bukhari - Ikrama عكرمة (Sahih al-Bukhari)
`Uthman bin `Abdullah bin Mauhab said, “My people sent me with a bowl of water to Um Salama.” Isra’il approximated three fingers (‘indicating the small size of the container in which there was some hair of the Prophet. `Uthman added, “If any person suffered from evil eye or some other disease, he would send a vessel (containing water) to Um Salama. I looked into the container (that held the hair of the Prophet) and saw a few red hairs in it,”
Grade: Sahih